2018
DOI: 10.1017/s0031182018002068
|View full text |Cite
|
Sign up to set email alerts
|

Dog hepatocytes are key effector cells in the liver innate immune response toLeishmania infantum

Abstract: Hepatocytes constitute the majority of hepatic cells, and play a key role in controlling systemic innate immunity, via pattern-recognition receptors (PRRs) and by synthesizing complement and acute phase proteins. Leishmania infantum, a protozoan parasite that causes human and canine leishmaniasis, infects liver by establishing inside the Kupffer cells. The current study proposes the elucidation of the immune response generated by dog hepatocytes when exposed to L. infantum. Additionally, the impact of adding l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
2
12
0
1
Order By: Relevance
“…In the current study, canine hepatic spheroids increased NO production in the presence of L. infantum , which was accompanied by the tendency to increase the expression of pro-inflammatory cytokines TNF-α and IL-6, indicating an immune recognition and activation of these cells towards the parasite. These findings are similar to what was previously observed by our group [ 24 ]. Interestingly, there are differences in the magnitude of the immune response to L. infantum generated by canine hepatic spheroids (3D) and traditional 2D cultured hepatocytes used in the previous study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the current study, canine hepatic spheroids increased NO production in the presence of L. infantum , which was accompanied by the tendency to increase the expression of pro-inflammatory cytokines TNF-α and IL-6, indicating an immune recognition and activation of these cells towards the parasite. These findings are similar to what was previously observed by our group [ 24 ]. Interestingly, there are differences in the magnitude of the immune response to L. infantum generated by canine hepatic spheroids (3D) and traditional 2D cultured hepatocytes used in the previous study.…”
Section: Discussionsupporting
confidence: 93%
“…Canine ( Canis lupus familiaris , n = 10) hepatocytes were isolated by a two-step perfusion protocol followed by collagenase digestion and Percoll ® gradient centrifugation, as previously described [ 3 , 4 , 24 ]. Briefly, a liver lobule was cleaned of internal blood by perfusion, and tissue digestion was performed with collagenase H (Roche Diagnostics, Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we provide evidence that parasite-derived components, can trigger IL-10 production by hepatocytes from non-infected animals, indicating that they can sense and respond to the presence of trypanosomes. In this context, in another parasitic model, it was recently shown that hepatocytes can respond to Leishmania infantum infection by the activation of inflammatory mechanisms and the production of IL-10 in order to balance the inflammatory response and avoid cell damage [42].…”
Section: Discussionmentioning
confidence: 99%